Serum Thyroid Hormone Antibodies Are Frequent in Patients with Polyglandular Autoimmune Syndrome Type 3, Particularly in Those Who Require Thyroxine Treatment - Vita, Roberto; Santaguida, Maria Giulia; Virili, Camilla; Segni, Maria; Galletti, Marina; Mandolfino, Mattia; Di Bari, Flavia; Centanni, Marco; Benvenga, Salvatore (Frontiers in Endocrinology, 2017)
Polyglandular autoimmune syndrome (PAS) type 3 consists of autoimmune thyroid disease (AITD) coexisting with ≥1 non-thyroidal autoimmune disease (NTAID) other than Addison’s disease and hypoparathyroidism. We evaluated the prevalence and repertoire of thyroid hormones antibodies (THAb) in PAS-3 patients. Using a radioimmunoprecipation technique, we measured THAb (T3IgM, T3IgG, T4IgM, and T4IgG) in 107 PAS-3 patients and 88 controls (patients with AITD without any NTAID). Based on the selective coexistence of AITD with one NTAID (chronic autoimmune gastritis, non-segmental vitiligo or celiac disease), patients were divided into group 1 (chronic autoimmune gastritis positive, n = 64), group 2 (non-segmental vitiligo positive, n = 24), and group 3 (celiac disease positive, n = 15). At least one of the four THAb was detected in 45 PAS-3 patients (42.1%) and 28 controls (31.8%, P = 0.14), with similar rates in the three PAS-3 groups. The rates of T3Ab, T4Ab, and T3 + T4Ab were similar in groups 1 and 2, while in group 3, T3Ab was undetected (P = 0.02). In PAS-3 patients, the rate of levothyroxine treatment was greater in THAb-positive patients compared to THAb-negative patients (76.7 vs. 56.1%, P = 0.03, RR = 1.4, 95% CI 1.03–1.81). Not unexpectedly, levothyroxine daily dose was significantly higher in group 1 and group 3, namely in patients with gastrointestinal disorders, compared to group 2 (1.9 ± 0.4 and 1.8 ± 0.3 vs. 1.5 ± 0.2 μg/kg body weight, P = 0.0005 and P = 0.004). Almost half of PAS-3 patients have THAb, whose repertoire is similar if chronic autoimmune gastritis or celiac disease is present. A prospective study would confirm whether THAb positivity predicts greater likelihood of requiring levothyroxine treatment.